Comparison of Sport Massage And Ice Bath on Lower Extremity Muscle Recovery Post-Training In Futsal Extracurricular Students of SMA Muhammadiyah 5 Jakarta - Cheroni, Ahmad Heraldi; Yuliana, Ela; Mitsalina, Dinan; Oktafiranda, Nadya Dwi (Jurnal Pendidikan Jasmani (JPJ), 2025)
In futsal sports, the lower extremities are predominantly used, so that after training or competing, muscle fatigue is often complained of, especially in the lower extremities. Recovery is an important aspect that must be done after training because it accelerates the loss of fatigue and reduces the risk of injury during training or competition. This study aims to compare sports massage and ice bath on lower extremity muscle recovery after training in futsal extracurricular at students at SMA Muhammadiyah 5 DKI Jakarta. The method in this study used a quasi-experimental approach with a two-group pretest and posttest design. The population in this study were students who participated in futsal extracurricular training at SMA Muhammadiyah 5. The sample in this study was determined using the total sampling technique, and the sample used was 26 students, then divided into 2 treatment groups. The data collected in this study were the level of fatigue using an instrument in the form of a questionnaire with a scale of 1-5, and the Delayed Onset Muscle Soreness (DOMS) pain scale using the Numeric Rating Scale (NRS) instrument with a scale of 0-10. The data analysis technique used the Wilcoxon Test for paired groups and the Mann Whitney test for unpaired groups. Based on the results of data analysis, the sports massage treatment group and the ice bath treatment group each had an effect on lower extremity muscle recovery, which was indicated by a decrease in fatigue levels between before and after treatment (p <0.05). The results of the comparison test showed no significant difference between the results of the decrease in fatigue levels in the sports massage group and the ice bath group (p>0.05). However, in terms of percentage, the decrease in fatigue levels after exercise, the sports massage group had a higher percentage decrease, which was 80.65%, compared to the ice bath group of 74.26%. Another result of this study, namely based on the results of the comparison test between the DOMS pain scale 24 hours after exercise in the sports massage and ice bath groups, there was no significant difference in results (p>0.05). Thus, sports massage and ice bath recovery can be used as post-exercise recovery strategies and can help prevent pain due to DOMS and shorten muscle recovery time